2020
DOI: 10.1111/iju.14382
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose rituximab induction therapy is effective in immunological high‐risk renal transplantation without increasing cytomegalovirus infection

Abstract: To analyze the effect and impact of low-dose rituximab induction therapy on cytomegalovirus infection in living-donor renal transplantation. Methods: A total of 92 recipients undergoing living-donor renal transplantation at Okayama University Hospital from May 2009 to August 2018 were evaluated retrospectively. Indications for preoperative rituximab (200 mg/body) were the following: (i) ABO major mismatch; (ii) ABO minor mismatch; (iii) donor-specific anti-human leukocyte antigen antibody-positive; and (iv) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(62 reference statements)
0
2
1
Order By: Relevance
“…In terms of neutropenia, the 25% rate of grade 3 neutropenia for the non‐rituximab group in the present study seems higher compared with 1–4% of severe leukopenia observed in prospective trials 1 . The authors consider that it can be attributed to mycophenolate mofetil, and that low‐dose rituximab does not increase the risk of neutropenia, even if used with mycophenolate mofetil.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…In terms of neutropenia, the 25% rate of grade 3 neutropenia for the non‐rituximab group in the present study seems higher compared with 1–4% of severe leukopenia observed in prospective trials 1 . The authors consider that it can be attributed to mycophenolate mofetil, and that low‐dose rituximab does not increase the risk of neutropenia, even if used with mycophenolate mofetil.…”
contrasting
confidence: 57%
“…In this issue of International Journal of Urology , Yoshinaga et al . reported the clinical outcomes of 59 immunologically high‐risk living‐donor renal transplant recipients who received a dose (200 mg/body) of preoperative rituximab 1 . Immunologically high‐risk patients were defined as having ABO major/minor mismatches, pre‐formed donor‐specific antigen or focal segmental glomerulosclerosis.…”
mentioning
confidence: 99%
“…As KT protocols vary across countries and regions, the vaccine e cacy has not been fully validated in KT recipients in Japan. In Japan, ABO blood-type incompatible (ABOi) KT protocols with strong immunosuppression strategies are necessary due to the absence of donor exchange programs and the serious donor shortage [9][10][11][12][13] . Currently, one-third of the recipients undergo ABOi KT with rituximab desensitization 13 .…”
Section: Introductionmentioning
confidence: 99%